Bifunctional ionic liquid and conducting ceramic co-assisted solid polymer electrolyte membrane for quasi-solid-state lithium metal batteries - Xie, Zhengkun; Wu, Zhijun; An, Xiaowei; Yoshida, Akihiro; Wang, Zhongde; Hao, Xiaogang; Abudula, Abuliti; Guan, Guoqing (Journal of Membrane Science, 2019)
Development of solid polymer electrolytes (SPEs) with high thermal and mechanical stability and fast ion conductivity is the key for high-performance lithium metal batteries (LMBs) with high safety. In this work, a flexible poly-(ethylene oxide) (PEO)-lithium bis(trifluoromethanesulfonyl)imide) (LiTFSI) SPE assisted with a bifunctional ionic liquid (IL) of tetrabutylphosphonium 2-hydroxypyridine (TBPHP) as well as a garnet-type fast-ion conducting ceramic of Li6.4La3Zr1.4Ta0.6O12 (LLZTO) was fabricated via a solvent-free procedure and applied for the LMBs. It is found that the tetrabutylphosphonium cation (TBP+) and 2-hydroxypyridine anion (HP−) of IL effectively tuned the crystallinity of PEO and enhanced lithium ion (Li+) transference, respectively, and the TBPHP and LLZTO played a synergistic role in improving the performance of SPEs. Meanwhile, the density functional theory (DFT) study was performed to understand the interaction between TBPHP and LiTFSI. As a result, the obtained PEO8-LiTFSI-TBPHP-12.5% LLZTO composite SPE possessed a high ionic conductivity of 9.39 × 10−4 S cm−1 at 50 °C and a wide electrochemical stability window (more than 5 V) with significantly promoted uniform Li plating/stripping properties. The quasi-solid-state-LMBs assembled with LiFePO4 cathode also rendered excellent cycling stability with a high discharge capacity above 150 mA h·g−1 even after 100 cycles at 0.2 C and 50 °C. Besides, the fabricated flexible pouch cell showed excellent performance. It is expected that such a bifunctional ionic liquid and conducting ceramic co-assisted polymer composite could be a promising solid electrolyte for the next-generation of safe LMBs. [Display omitted] •Bifunctional ionic liquid and ceramic filler enhanced electrolyte was proposed.•Effect of ionic liquid was proved by experiment and DFT calculations.•The electrolyte showed superior ionic conductivity and fast ion transport.•The battery with this electrolyte showed improved capacity and cycling stability.